2018
DOI: 10.1002/epi4.12266
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability in visual identification of interictal high‐frequency oscillations on electrocorticography and scalp EEG

Abstract: SummaryHigh‐frequency oscillations (HFOs), including ripples (Rs) and fast ripples (FRs), are promising biomarkers of epileptogenesis, but their clinical utility is limited by the lack of a standardized approach to identification. We set out to determine whether electroencephalographers experienced in HFO analysis can reliably identify and quantify interictal HFOs. Two blinded raters independently reviewed 10 intraoperative electrocorticography (ECoG) samples from epilepsy surgery cases, and 10 scalp EEG sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…challenging and jeopardize its interrater reliability if raters have variable experience [43]. Our interrater reliability of visual HFOs analysis was generally favorable (our lowest kappa value was 0.65) and compatible to previous results from experienced HFOs readers [40]. The existence of physiologic HFOs has also been described and differentiating physiologic from pathologic HFOs can be challenging in intracranial recording [44,45].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…challenging and jeopardize its interrater reliability if raters have variable experience [43]. Our interrater reliability of visual HFOs analysis was generally favorable (our lowest kappa value was 0.65) and compatible to previous results from experienced HFOs readers [40]. The existence of physiologic HFOs has also been described and differentiating physiologic from pathologic HFOs can be challenging in intracranial recording [44,45].…”
Section: Discussionsupporting
confidence: 80%
“…Due to low signal-to-noise ratio, some of the events were difficult to be differentiated from artifacts and deemed "undetermined". This seems an inherent limitation of scalp HFOs analysis [40].…”
Section: Discussionmentioning
confidence: 99%
“…This work indicates that our deep learning approach can overcome issues including poor inter-rater reliability of HFO classification among human experts and their time constraints of analysis. Although our interrater reliability in this study was favorable as previously reported, 50 we expect the agreement will likely diminish when raters are from different institutions or have different experience levels. 15, 23 Using HFO analysis, we may identify brain tissue that needs to be removed during surgery without human experts’ effort if an algorithm was trained from large enough EEG data from patients with known post-operative outcomes.…”
Section: Discussionsupporting
confidence: 65%
“…If the values for HFO detection are not established and fixed, it will remain impossible to translate techniques relying on the automatic detection of HFOs to any patient population; this is a major and pressing limitation of most studies involving HFO analysis. With this understanding, however, the inter-rater reliability and generalizability of even manual detection of HFOs has been questioned, (51, 52) [but, also, (53)] so this is not a concern limited to algorithmic methods, but may represent a constraint related to problem definition. Furthermore, while we note that the limitation of a 512 Hz sampling rate may have been insufficient to accurately measure higher-frequency phenomena, the 200 Hz 3-dB cutoff on our anti-aliasing filter is still considered in the middle of the "ripple" band (54).…”
Section: Interictal Datamentioning
confidence: 99%